Regional Responses to Disasters : Practice But Not Policy? - Jones, Catherine (2018)
July 2018 was a month of practical challenges for responders to humanitarian disasters in the wake of the collapsed dam in Laos, the ongoing challenges resulting in the loss of civilian lives in Myanmar, and the earthquake in Indonesia. It is timely to ask who responds and how these responses are coordinated and monitored.